1980
DOI: 10.1161/01.cir.62.6.1188
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative difference in "critical" stenosis between right and left coronary artery in man.

Abstract: Coronary artery stenoses that limit blood flow below demand are considered critical. In this comparative study we investigated whether the same degree of stenosis in either the proximal third of the right coronary artery (RCA) or the proximal third of the left anterior descending artery (LAD) causes critical flow reduction. Lesions were quantified from 35-mm cinefilms in multiple projections using a vernier caliper. These morphometric measurements were correlated with various manifestations of critical flow re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 66 publications
1
9
0
2
Order By: Relevance
“…3, as the stenosis severity increases, the difference between the time-averaged values over one cardiac cycle, the so called ''mean value'', of inlet and outlet pressure increases as well. Several experimental studies indicate that pressure gradients or changes in the blood flow can be detected when the cross-sectional luminal area is reduced by 80% (Rafflenbeul et al, 1980;Berguer et al, 1974;Mates et al, 1978;Feldman et al, 1978;May et al, 1963). But, in the actual circulation, studies have shown that resting flow is unaffected and remains constant until coronary lumen area is reduced by more than 96-99%.…”
Section: Resultsmentioning
confidence: 99%
“…3, as the stenosis severity increases, the difference between the time-averaged values over one cardiac cycle, the so called ''mean value'', of inlet and outlet pressure increases as well. Several experimental studies indicate that pressure gradients or changes in the blood flow can be detected when the cross-sectional luminal area is reduced by 80% (Rafflenbeul et al, 1980;Berguer et al, 1974;Mates et al, 1978;Feldman et al, 1978;May et al, 1963). But, in the actual circulation, studies have shown that resting flow is unaffected and remains constant until coronary lumen area is reduced by more than 96-99%.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion criteria for the study were age (18 years or older), ability to communicate in English or French, and ability to provide written informed consent. Clinically significant CAD was said to be present in any patient with 50% or greater narrowing of one or more of the major coronary arteries, since it has been shown that this leads to a significant reduction in flow (Rafflenbeul, Urthaler, Lichtlen, & James, 1980). Based on the results of the angiogram, sixty-four percent (n = 123) of the patients were classified with clinically significant CAD, 16% (n = 30) with nonsignificant CAD, and 21% (n = 40) with normal arterial functioning.…”
Section: Participantsmentioning
confidence: 99%
“…The control group comprised 21 patients with typ ical angina pectoris who were shown to have signifi cant coronary artery disease [15,16] (more than 50% reduction in intraluminal diameter of at least one major coronary artery), and who had undergone angi ography during the same period of time. Thirteen were female, 8 male, and they were aged 36-65 years (mean 50).…”
Section: Control Group (Significant Coronary Artery Disease)mentioning
confidence: 99%